2013
DOI: 10.1186/1756-8722-6-90
|View full text |Cite
|
Sign up to set email alerts
|

STAT inhibitors for cancer therapy

Abstract: Signal Transducer and Activator of Transcription (STAT) proteins are a family of cytoplasmic transcription factors consisting of 7 members, STAT1 to STAT6, including STAT5a and STAT5b. STAT proteins are thought to be ideal targets for anti-cancer therapy since cancer cells are more dependent on the STAT activity than their normal counterparts. Inhibitors targeting STAT3 and STAT5 have been developed. These included peptidomimetics, small molecule inhibitors and oligonucleotides. This review summarized advances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
145
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(147 citation statements)
references
References 87 publications
(74 reference statements)
2
145
0
Order By: Relevance
“…41). Using excellent wet chemistry and computer-assisted methods, many compounds have been created that attack this target, several successfully, reducing tyrosine 705 phosphorylation, inhibiting tumor cells in culture, and even effecting a modest inhibition of human tumor xenografts in mice (20,(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…41). Using excellent wet chemistry and computer-assisted methods, many compounds have been created that attack this target, several successfully, reducing tyrosine 705 phosphorylation, inhibiting tumor cells in culture, and even effecting a modest inhibition of human tumor xenografts in mice (20,(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…68 Constitutive activation of the pathway in response to deregulate upstream signals is commonly observed in diverse cancers including dead and neck and laryngeal tumors. [69][70][71] This constitutive activation of the pathway has been involved in proliferation and survival of tumors as well as resistance to chemo and radiotherapy. 70,71 Recent works indicate that STAT signaling also contributes to therapy resistance by modulating also the microenvironment.…”
Section: Dna Damage Repair Biomarkersmentioning
confidence: 99%
“…[69][70][71] This constitutive activation of the pathway has been involved in proliferation and survival of tumors as well as resistance to chemo and radiotherapy. 70,71 Recent works indicate that STAT signaling also contributes to therapy resistance by modulating also the microenvironment. 72 ERp57 (GRP58) is a chaperone that regulated proper folding of glycoproteins.…”
Section: Dna Damage Repair Biomarkersmentioning
confidence: 99%
“…These include the inhibition of transcription factor gene expression using antisense oligonucleotides, inhibition of the STAT3-DNA binding domain using decoy oligonucleotides or posttranscriptional gene-silencing using small interfering RNA (Table 1) [15]. AZD9150, an antisense oligonucleotide inhibitor of STAT3, was well-tolerated and demonstrated single-agent antitumor activity against treatment-refractory lymphomas and NSCLC in a phase I clinical trial [12].…”
Section: Existing Strategies In Stat3 Inhibitionmentioning
confidence: 99%
“…Numerous preclinical studies have confirmed their mode of action and downstream effects on tumor cell inhibition in a variety of cell lines and animal models. However, most of these compounds have yet to be explored in clinical studies due to concerns over their relative lack of potency and selectivity [15]. OPB-51602 and OPB-31121 are the only agents in this class to have reached early phase clinical trials in both advanced solid malignancies.…”
Section: Existing Strategies In Stat3 Inhibitionmentioning
confidence: 99%